Жадьылись мешок: выжыкылъес / Вениамин Ившин - Ившин Вениамин Никонорович (Удмуртия, 2012)
Экземпляры: ф.2 (2) (20141215) / Инвентарный номер: бр. / Цена: 91.25 / Авт.знак: И 25 / ГРНТИ: 17.82.93 / ББК: 84(2Рос.Удм)6